Low-order dynamical model and distributed coordinated model predictive control for multi-stage belt conveyor systems. (April 2023) - Yang, Chunyu; Chen, Bin; Bu, Lingchao; Zhou, Linna; Ma, Lei
Abstract: This work studies a distributed economic model predictive control (DEMPC) approach for multi-stage belt conveyor (BC) systems based on a novel low-order model. First, the existing BC finite element dynamic model is reduced to a low-order model with five micro-element segments. In describing the speed and acceleration range of the BC, the low-order model is consistent with the original model. Then, a DEMPC method is proposed for multi-stage BC systems. In this method, the state information of the adjacent BCs is used to express the collaborative cost function for the local optimization control problem. By using the obtained method, the economic performance is improved, and the energy consumption is reduced. Finally, hardware-in-the-loop simulation tests are utilized to demonstrate the benefits of the results gained. Highlights: A low-order dynamical model is proposed for the single belt conveyor. A collaborative cost function is constructed for the multistate belt conveyor. A distributed economic model predictive control of multistage belt conveyor is given. A hardware-in-the-loop experiment system is designed to verify the proposed methods.